Examining the role of the temporo-parietal network in memory, imagery, and viewpoint transformations - Dhindsa, Kiret; Drobinin, Vladislav; King, John; Hall, Geoffrey B.; Burgess, Neil; Becker, Suzanna (Frontiers in Human Neuroscience, 2014)
The traditional view of the medial temporal lobe (MTL) focuses on its role in episodic memory. However, some of the underlying functions of the MTL can be ascertained from its wider role in supporting spatial cognition in concert with parietal and prefrontal regions. The MTL is strongly implicated in the formation of enduring allocentric representations (e.g. O’Keefe (1976); Ekstrom et al. (2003); King et al. (2002)). According to our BBB model (Byrne et al. (2007)), these representations must interact with head-centered and body-centered representations in posterior parietal cortex via a transformation circuit involving retrosplenial areas. Egocentric sensory representations in parietal areas can then cue the recall of allocentric spatial representations in long-term memory and, conversely, the products of retrieval in MTL can generate mental imagery within a parietal ’window’. Such imagery is necessarily egocentric and forms part of visuospatial working memory, where it can be manipulated for the purpose of planning/imagining the future. Recent fMRI evidence (Lambrey et al. (2012); Zhang et al. (2012)) supports the BBB model. To further test the model, we had participants learn the locations of objects in a virtual scene and tested their spatial memory under conditions that impose varying demands on the transformation circuit. We analyzed how brain activity correlated with accuracy in judging the direction of an object 1) from visuospatial working memory (we assume working memory due to the order of tasks and the consistency viewpoint, but long-term memory is also possible), 2) after a rotation of viewpoint, or 3) after a rotation and translation (judgement of relative direction). We found performance-related activity in both tasks requiring viewpoint rotation in the core medial temporal to medial parietal. These results are consistent with the BBB model and shed further light on the mechanisms underlying spatial memory, mental imagery and viewpoint tranformations